2017
DOI: 10.1371/journal.pone.0185263
|View full text |Cite
|
Sign up to set email alerts
|

Global reaction to the recent outbreaks of Zika virus: Insights from a Big Data analysis

Abstract: ObjectiveThe recent spreading of Zika virus represents an emerging global health threat. As such, it is attracting public interest worldwide, generating a great amount of related Internet searches and social media interactions. The aim of this research was to understand Zika-related digital behavior throughout the epidemic spreading and to assess its consistence with real-world epidemiological data, using a behavioral informatics and analytics approach.MethodsIn this study, the global web-interest and reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 29 publications
4
52
1
2
Order By: Relevance
“…From an epidemiological standpoint, our results are consistent with the recent findings of Bragazzi et al 34 , who analyzed various data streams to measure the global reaction to the 2015-2016 ZIKV outbreaks in different countries. Similarly, we did not find any statistically significant correlation between the attention to Wikipedia pages and the ZIKV incidence data in the U.S.…”
Section: Discussionsupporting
confidence: 91%
“…From an epidemiological standpoint, our results are consistent with the recent findings of Bragazzi et al 34 , who analyzed various data streams to measure the global reaction to the 2015-2016 ZIKV outbreaks in different countries. Similarly, we did not find any statistically significant correlation between the attention to Wikipedia pages and the ZIKV incidence data in the U.S.…”
Section: Discussionsupporting
confidence: 91%
“…However, the percentage of internet users was high in most of the studied countries, only in Nicaragua (25%) the internet penetration was substantially lower compared to that in the other countries and thus could have potentially influenced our results [16]. Despite this, a study on the worldwide Zika-related digital behaviour found that activity came mainly from the CSA region, even though the Zika outbreak breached beyond this region and received global news coverage [27]. Second, the observed interest level is limited to those who use google as a search engine.…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…To begin, social media is sometimes used as a tool for digital epidemiology: publicly available and crowdsourced is analyzed to better detect and monitor disease outbreaks (Chou et al 2013;Elkin, Topal and Gurkan 2017;Schomberg et al 2016;Sinnenberg et al 2017;Woo et al 2017). Secondly, social media has been analyzed to explore the online content visualized by users in order to better understand the information that they consume, but usually without consideration for the manner in which this is received and appreciated (Basch et al 2015;Bragazzi et al 2017). Thirdly, some researchers have explored rumors and misinformation circulating on social media, and highlighted the importance for public health authorities to analyze such conversations and counteract the spread of false information by acting as moderators (Yang, Horneffer, and DiLisio 2013;Nagpal et al 2015;Sharma et al 2017).…”
Section: Introductionmentioning
confidence: 99%